From Machine Enclosure to Pressurised Build Chamber - Enabling Additive Manufacturing of Large Components in Inert Environments - Karlsson, Evelina; Wikström, Anton (My University, 2026)
Additive manufacturing (AM) of large titanium components for the aerospace industry requires inert environments to prevent oxidation and contamination to ensure material integrity. As the aerospace manufacturers scale up titanium AM, maintaining these inert atmospheres becomes increasingly challenging. Permanova Lasersystem AB is developing a scaled up laser directed energy deposition (L-DED) system with a larger and reversible build plate to enable larger and more efficient builds and improved residual stress control. However, the current tent-based inert enclosure cannot be expanded to work with the new build plate. This thesis explores how the existing laser safety enclosure surrounding the system can be adapted to also function as an overpressurised inert enclosure by assessing what overpressure it should withstand and maintain, how it responds to it, what the biggest problems for maintaining it are, and how different solutions for solving those problems compare. Interviews, standards review and state-of-theart analysis established that a pressure differential of 50 Pa prevents ambient air infiltration; therefore, 100 Pa was selected as the design pressure to incorporate a safety factor of two and maintain recommended engineering margins. Leakage assessment revealed critical leakage paths at the floor interface, ceiling, corners, and panel joints, while structural simulations identified weaknesses in the active protection panels and part of the skeleton. Based on these findings, sealing and reinforcement concepts were developed and evaluated. The final solution was to implement metal plates and L-profiles together with a polyurethane sealant for covering the major leakage paths, a fully sealed active panel to not only prevent leakage but also to increase stiffness and an additional roof beam to eliminate deflection. The results demonstrate that the existing laser enclosure can effectively be adapted into a large, overpressurised inert enclosure without extensive redesign.
Keywords: overpressure; additive manufacturing; sealing; machine enclosure